The human rights and the Brazilian prisons among the Covid-19 pandemic (Delito y Sociedad, 2021)
The purpose of the paper is to present the effects of the Covid-19 in the Brazilian prisons, based on official data, public documents, press materials and studies published on this subject. Initially, the main problems in terms of human rights violations that usually occur in these environments will be presented. Next, the measures adopted by Brazilian states to prevent the new coronavirus from harming prisoners will be analyzed. In addition, the number of people infected and killed by the coronavirus inside and outside the detention facilities will be compared, as well as the press reports on the national prison context during the health crisis. In conclusion, despite the pandemic, the imperatives of public safety and discipline supersede the value of the lives of people deprived of liberty. In the current context, more prison violence, deaths and people infected by the virus are expected. However, many of these episodes may not be public, since, with the pandemic, Brazilian prisons are even more isolated from the society
Keywords: Brazil; prisons; pandemic; Covid-19; human rights